Pengaruh Attention, Interest, Desire dan Action Terhadap Keputusan Pembelian Sepeda Motor Merek Honda pada PT. Capella Dinamik Nusantara Takengon Kabupaten Aceh Tengah - Abd. Jalil. M; Sabri Sabri; Bambang Surahman; Ramiati Ramiati; Patimah Aprilliani (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the effect of attention, interest, desire, and action on purchasing decisions for Honda brand motorcycles. The population in this study was 320 people and the sample in this study was 76 people calculated using the Slovin formula as consumers of PT. Capella Dinamik Nusantara Takengon. The data analysis method was in the form of validation tests and reliability tests and using classical assumption tests, then re-analyzed using multiple linear regression, hypothesis testing and determination coefficient tests. The results showed that the variables attention, interest, desire and action, the four variables partially had a significant effect on purchasing decisions. All independent variables had a simultaneous and significant effect on purchasing decisions for Honda brand motorcycles at PT. Capella Dinamik Nusantara Takengon, Central Aceh Regency.